A new species of Moraria (Crustacea: Copepoda: Harpacticoida) from the Laurentian Great Lakes - Reid, Janet W.; Lesko, Lynn T. (Zootaxa, 2003)
Moraria hudsoni n. sp. is described from Trails End Bay in Lake Michigan and Prentiss Bay in Lake Huron, Michigan, USA. The new species differs from its congeners in chaetotaxy, body ornamentation, and other characters. We review published records of members of Moraria from North and Central America; no species is known from South America. Species of this genus have been found in the mountains of southern Mexico, Guatemala, and Honduras, but none of these has been validly described. In North America, eight species have been recorded from Alaska, Canada, and the conterminous USA as far south as North Carolina. We report new geographical records of M. affinis from Virginia, and of both M. cristata and M. virginiana from Maryland and Virginia. We provide a tabular key to aid in identification of the named species of Moraria in North America.